Clinical researchThe impact of the Adjustable PM Positioner appliance in the treatment of obstructive sleep apnoea - Giannasi, Lílian C.; de Mattos, Luiz C.; Magini, Márcio; Costa, Maricília S.; de Oliveira, Cláudia S.; de Oliveira, Luis V.F. (Archives of Medical Science, 2008)
Introduction: Obstructive sleep apnoea (OSA) is regarded as a potentially life-threatening condition characterized by repeated narrowing/collapse of the pharyngeal walls during sleep. The efficacy of oral appliances (OA) in the treatment of sleep-disordered breathing has been rigorously investigated and proven in the last decades. Due to patients preferring OA therapy, many designs have been developed, including the Adjustable PM Positioner. The aim of this study was to evaluate the efficacy of the Adjustable PM Positioner in the treatment of obstructive sleep apnoea, comparing polysomnograms (PSG) pre-treatment and with the OA in situ. Material and methods: Twenty-nine patients were enrolled in this study. The sample was divided into two groups: the non-obstructive sleep apnoea (NOSA) group, with 5 snoring patients, and the OSA group, with 24 patients. They used the appliance for 6 months and then underwent another PSG with the appliance in situ. Results: The results showed no statistically significant differences in all variables of the NOSA group, except for the presence of snoring, which was reduced, according to PSG findings. For the OSA group the results for apnoea/hypopnoea index (AHI), rapid eye movement (REM) sleep, nadir, mean and basal oxyhaemoglobin saturation (SaO 2 ), showed statistically significant differences. The presence of snoring also decreased according to PSG findings. Conclusions: We conclude that the adjustable PM Positioner is effective in the treatment of OSA comparing baseline and post-treatment respiratory variables.